Fixed-dose combination therapy of candesartan cilexetil and amlodipine besilate for the treatment of hypertension in Japan. (May 2012) - Yasuno, Shinji; Fujimoto, Akira; Nakagawa, Yasuaki; Kuwahara, Koichiro; Ueshima, Kenji
Hypertension is one of the most prevalent disorders and the largest contributor to global mortality. The aim of antihypertensive treatment is to reduce the risk of cardiovascular morbidity and mortality by lowering increased blood pressure (BP) to target levels. Despite progress in antihypertensive drug development, BP control remains suboptimal. Accumulating evidence has shown that fixed-dose combination therapy is better in terms of BP control than increasing the dose of one drug or its corresponding combination. Fixed-dose combinations of an angiotensin receptor blocker, candesartan cilexetil, and a calcium channel blocker, amlodipine besilate (candesartan/amlodipine 8/2.5 or 8/5 mg), were approved in Japan for once-daily oral administration in hypertensive patients. Recent data showed that a fixed-dose combination of candesartan and amlodipine lowered BP safely and rapidly, providing a potential opportunity to improve the rate of BP control. Further studies are needed to determine whether this will lead to improvements in long-term clinical outcomes.